PELATIHAN DIGITAL MARKETING DAN CARA MUDAH MEMBUAT LAPORAN KEUANGAN USAHA UNTUK ANGGOTA WIRAUSAHA TANGGUH BUMI INTAN PARI (WITPARI) KARANGANYAR - Ramadhian Agus Triono Sudalyo; Nurita Elfani Prasetyaningrum; Jani Kusanti (LPPM Universitas Bina Bangsa, 2023)
The digital era makes most human activities carried out online as well as product marketing. The number of digital platforms makes it easier for customers to be able to get the desired goods without having to leave the house. Over time, digital platforms are increasingly in demand so most customers prefer to shop online. This certainly makes entrepreneurs, especially MSMEs, have to keep up with technological developments to maximize sales. Then no less important is the management of business finances to obtain optimal business profits. Digital marketing, one of which is a promotional video, is one way to be able to market products with a wider range on the right marketing channels. However, not all MSME entrepreneurs know how to produce promotional videos that attract and attract consumer interest, including choosing the right media channels to reach an effective and productive market. In addition to digital promotional needs, MSME actors must understand how to prepare financial reports, so that business actors understand targeted financial governance. One of the layers of society that requires the implementation of digital marketing and financial reports is Witpari (Wirausaha Tangguh Bumi Intan Pari) Karanganyar. With the existence of digital marketing and promotion facilities as well as the preparation of good financial reports, Witpari can obtain a wider marketing reach and an orderly financial management process. Therefore, the academic community of the University of Surakarta intends to provide education to Witpari regarding the implementation of promotional videos and business financial reports that can be used to market products and manage business finances. Training is provided through Community Service activities carried out by lecturers